Financial aid data: indebtedness of M'83 - Tufts University (Tufts Archival Research Center, 2014)
slides (photographs). Include average indebtedness of M1981 and M1982, Indebtedness of M1983 includes Tufts, Boston University, Harvard, Umass, and national